Effects of air volume and pre-oxidation on re-ignition characteristics of bituminous coal. (15th February 2023) - Liu, Qiqi; Sun, Lulu; Liu, Zhenyi; Wang, Gang; Ma, Jiayu
Abstract: Coal spontaneous combustion (CSC) seriously threatens the safety of coal mines. To reduce the spontaneous combustion risk of residual oxidized coal in goaf near coal seam and thick coal seam, it is necessary to study the re-ignition process of coal in depth. The re-ignition process of bituminous coal under different pre-oxidation temperatures and air volume rates was tested by temperature-programmed experiments. The gas index and re-ignition characteristic parameters of low-temperature oxidized coal were analyzed. The results show that CO production, C2 H4 concentration, and Graham's fire coefficient (R2, R3 ) can be used as indicator gases to predict the CSC process. Meanwhile, the oxygen consumption rate and heat release intensity of raw coal and oxidized coal have a good exponential relationship with the coal temperature. In addition, during the slow oxidation stage of bituminous coal, the pre-oxidation process and the increased air volume can increase the oxygen consumption and heat release and reduce the activation energy, which aggravates the risk of spontaneous combustion. The results can enrich the research on the re-ignition characteristics of oxidized coal and can be applied to the management and control of CSC. Highlights: The gas index prediction method of the bituminous coal re-ignition process is proposed. The gas index and spontaneous combustion characteristics of raw coal and oxidized coal are compared. The apparent activation energies of raw coal and oxidized coal at different oxidation stages are obtained. The influence of per-oxidation temperature and ventilation on the re-ignition process of oxidized coal is determined.